TANGGUNG JAWAB PELAKU USAHA TERHADAP PAKAIAN BEKAS IMPOR BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN ( Studi Kasus Pasar Datuk Rubiah) - Jusma Dona; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The rapid economic development has resulted in various types and variations of goods and / or services. With the support of technology and information, consumer needs are simple, and the relationship between consumers and traditional society is relatively simple. Where consumers and producers can meet face-to-face. The modern society produces consumer goods in bulk, thus creating mass consumers as well. The purpose of thesis writing is: firstly, to know the impact on the business actors with the Regulation of the Minister of Trade of the Republic of Indonesia No. 51 / M-DAG / PER / 7/2015 on the prohibition of second-hand clothing import, secondly to know the responsibility of the imported clothing business players based on the Law -Indonesia Number 8 Year 1999 About Consumer Protection.This type of research can be classified in the type of sociological juridical legal research and data collected by seeking information based on questionnaires, interviews and literature related to the research. This research was conducted in Datuk Rubiah market Kota Bagansiapiapi whereas population and sample were all parties related to the problem under study. In this study the data used, in this study is by observation, interview and literature studyFrom the research result of the problem there are two main things that can be concluded, firstly, the impact of business actor on Ministerial Regulation No. 51 / M-DAG / PER / 7/2015, business actor opinion is reduced, Second, business actor responsibility based on Law No. 8 year 1999 about consumer protection, they do not provide clear information, so that the rights of consumers are violated. warrant, the perpetrator must be aware of the Ministerial Regulation No. 51 / M-DAG / PER / 7/2015 Minister, for consumers should be more careful in buying and reading -Undonesia Number 8 Year 1999 About Consumer Protection.Keywords: Used Clothing - Responsibility - Consumer Protection